High Variability in Clinical and Histopathological Patterns of Abnormal Uterine Bleeding in Perimenopausal Women - Asifa Alia, Sabeena Umer, Shumaila Yasin, Shazia Roman, Nusrat Manzoor, Faiza Irshad, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The term "abnormal uterine bleeding" (AUB) refers to bleeding from the uterus that is either more than usual, occurs for a longer amount of time than normal, or occurs at an irregular time. All three of these factors can contribute to AUB. AUB can affect persons of any age and can manifest itself in a variety of ways. It is also one of the most common reasons that patients go to see their physicians because it is a presenting complaint or symptom. There is a wide variety of underlying reasons, some of which include fibromyoma, adenomyosis, endometrial polyp, ovarian tumour, pelvic inflammatory disease (PID), endometrial hyperplasia, endometrial cancer, hormonal imbalance (such as hypothyroidism), or hypothalamus pituitary illnesses. Place of Study: Rai Medical College Sargodha Duration of Study: November 2018 and March 2022 Methods: The Obstetrics and Gynecology department of RAI Medical College in Sargodha carried out this prospective observational study during the months of November 2018 and March 2022. One hundred and ten patients in all were given permission to take part in the research project after meeting the prerequisites for participation. Results: According to the statistics, the largest number of cases, 51.2%, fell within the age range of 41-50 years. The next largest number of cases, 28.9%, fell within the age range of 31-40 years. In total, there were 110 people who agreed to take part in the research. The average age of all of the patients was 44.87 years old, with a standard deviation of 9.45 years. According to the findings of our investigation, the most common mode of presentation was heavy menstrual bleeding, which was recorded in 54 cases (49.9%). This was followed by delayed menstrual bleeding, which was observed in 23 instances (20.9%). Endometrial hyperplasia was found in 16 (14.5%) of the patients, proliferative endometrium was found in 47 (42.7%) of the cases, secretory endometrium was found in 38 (34.5%) of the cases, and endometrial hyperplasia was found in 15 (13.6%) of the cases. Keywords: Abnormal uterine bleeding, histopathology, dysfunctional uterine bleeding